Oliver Twist. - Reiss, Anya (Oberon modern plays., 2017)
"He was born in the workhouse and should by rights have died there until he displayed such malice, such ingratitude, such downright greed good sir he was removed for fear of corrupting the other children."Discover the original story of Victorian London's most famous orphan, retold from Charles Dickens' novel for the stage by Anya Reiss. Oliver Twist, originally staged outdoors at Regent's Park Open Air Theatre, was created for everyone aged six and over.